Effect of diazoxide or glucagon on hepatic glucose production rate during extreme neonatal hypoglycaemia. Issue 9 (September 1987) - Mehta, A; Wootton, R; Cheng, K N; Penfold, P; Halliday, D; Stacey, T E
Abstract : The relation between hepatic glucose production rate (HGPR) and plasma concentrations of insulin and glucagon was investigated in four term neonates who had severe hypoglycaemia. The hepatic glucose production rate was less than 20% of normal for fasting term neonates in all four babies and yet insulin concentrations were never greater than 12 microU/ml; two babies had very low glucagon concentrations (less than 60 ng/l). Two further neonates with similar histories also had plasma glucagon concentrations that were also extremely low (less than 20 ng/l). A single intravenous bolus of glucagon caused a rapid rise in hepatic glucose production rate towards the normal range, which was sustained for many hours after the bolus had been given. Diazoxide given to one baby suppressed previously 'normal' insulin concentrations still further (4.2 to less than 1.6 microU/ml) and thereby restored the hepatic glucose production rate to normal. In view of the normal plasma insulin concentrations at a time when the hepatic glucose production rate was reduced, we feel that the absolute concentration of insulin may be less important than the insulin/glucagon molar ratio in the control of glucose homeostasis in this group of infants. The changing of this ratio by means of boluses of glucagon may be useful in preventing rebound hypoglycaemia, which so often occurs when dextrose infusions are reduced either accidentally or in an attempt to restart oral feeds.